2011
DOI: 10.1111/j.1526-100x.2010.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Variation in Ecophysiology of Three Dominant Prairie Grasses Used in Restoration: Cultivar Versus Non‐Cultivar Population Sources

Abstract: Dominant species play crucial roles in determining plant community structure and ecosystem function. Cultivars of the dominant prairie grasses are widely used in prairie restoration and are selected for characters such as high biomass production, increased reproductive output, and stress tolerance. Genetic differences exist between cultivar and non-cultivar population sources of dominant tallgrass prairie species, which may have implications for plant performance in prairie restoration. We measured net photosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 42 publications
2
45
1
1
Order By: Relevance
“…Moreover, while site influenced the germination for all species, the effects of both source type and seed mass on S. nutans germination varied among sites, as evidenced by significant interaction terms in statistical models. These findings are consistent with other studies that have found important differences among dominant grass species in their physiological performance, competitive ability, dominance and response to altered resource conditions such as reduced nitrogen and water availability (Silletti & Knapp ; Wilsey ; Klopf & Baer ; Lambert, Baer & Gibson ; Grman, Bassett & Brudvig ). The existence of such important differences among ‘ecologically similar’ species suggests that practitioners should be cautious when generalizing about restoration practices from studies of ‘similar’ grass species in prairie ecosystems.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, while site influenced the germination for all species, the effects of both source type and seed mass on S. nutans germination varied among sites, as evidenced by significant interaction terms in statistical models. These findings are consistent with other studies that have found important differences among dominant grass species in their physiological performance, competitive ability, dominance and response to altered resource conditions such as reduced nitrogen and water availability (Silletti & Knapp ; Wilsey ; Klopf & Baer ; Lambert, Baer & Gibson ; Grman, Bassett & Brudvig ). The existence of such important differences among ‘ecologically similar’ species suggests that practitioners should be cautious when generalizing about restoration practices from studies of ‘similar’ grass species in prairie ecosystems.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, plant diversity in restorations often decreases as productivity of dominant grasses increases (Baer et al . ; Wilsey ; Lambert, Baer & Gibson ; Gibson et al . ; Grman, Bassett & Brudvig ).…”
Section: Discussionmentioning
confidence: 99%
“…; Johnson, Vellend & Stinchcombe ; Schröder & Prasse ). There are differences between local ecotypes and cultivars in their competitive ability and physiological characteristics (Gustafson, Gibson & Nickrent ; Lambert, Baer & Gibson ; Wilson et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…First, while a cultivar approach may help restore some EFs (e.g. enhanced performance of cultivars may lead to increased productivity; Lambert, Baer & Gibson ), the development of cultivars can lead to a reduction in GD and therefore may diminish positive effects of GD on ecosystems. Secondly, cultivars may hybridize with surrounding, locally adapted genotypes leading to ‘genetic pollution’ (Lesica & Allendorf ; Rowe & Leger ; but see Casler et al .…”
Section: Approaches To Sourcing Propagules For Restorationmentioning
confidence: 99%